Wear and Corrosion of Wrought A6061 Aluminium Alloy in DOT3 Brake Fluid - Ajibola, Olawale; Ige, Oladeji; Olubambi, Peter (International Journal of Engineering and Technology, 2018)
The twofold impact of wear and corrosion on wrought A6061 alloy in hydraulic DOT3 brake fluid environment was studied. The wear studies were performed on the samples using a developed wear-jig. Weight loss corrosion test method was used to determine the corrosion rate of the wrought A6061 alloy samples immersed in the brake fluid for a total of 1680 hours. From the results of wear tests carried out on the A6061 alloy sample with brake oil, the highest wear value of 5.24x10-7 mg/mm2/cycle (approx.) was obtained from 6 N (approx) force after 130 minutes. The wrought A6061 alloy material demonstrated the highest corrosion rates nearly 3.0 x10-2 mg/mm2/yr within the early 168 hours of immersion in brake fluid. The result is practically lower than the corrosion rate of cast specimen in DOT3 brake oil or some other alloys immersed in other corrosive media that were previously reported in the literature. The results show that small amount of chemical corrosion is sufficient to cause and accelerate mechanical wear of the material in usage.